"It is a different world in here": collective identification and shared experiential knowledge between psychiatric inpatients. Issue 4 (21st January 2020) - Kessing, Malene L.
Abstract: This paper explores the social relations between inpatients in psychiatric wards. Combining Barker's (2002) concept of 'collective illness identity' with Nelson's (1993) concept of 'epistemological communities', I draw attention to the inpatients' collective identification and experiential knowledge. Through the analysis, three aspects of the inpatients' relationships are unfolded. First, how the inpatients, through bodily expressions and narrative accounts, construct a collective illness identity based on shared experiences of symptoms and suffering. Second, the ways in which the inpatients use their shared experiential knowledge to support one another and challenge the mental health professionals. Third, how the inpatients' reflections on the long‐term potential of their relationships reveal a number of concerns related to their continuation. Centrally, the paper points to the potential and challenges that arise from the inpatients' relations to one another and their embeddedness in a specific time and space. Empirically, the paper draws on five months of participant observation conducted in two psychiatric wards in Denmark and interviews with 14 psychiatric patients.